Acute psychiatric admissions from an out-of-hours Casualty Clinic; how do referring doctors and admitting specialists agree? - Hansen Vidje; Deraas Trygve S; Giæver Anton; Olstad Reidun (BMC, 2006)
Abstract Background Over the last decades there has been an increasing pressure on the acute psychiatric wards in Norway. The major contributor to psychiatric acute admissions at the University Hospital of North Norway in the city of Tromsø in 2001 was the GP-based Tromsø Casualty Clinic, only open out-of-hours. We explored all acute psychiatric referrals from Tromsø Casualty Clinic in 2001. The purpose of the study was to characterize the admissions and assess the agreement between the referring doctors and the hospital specialists according to the need for hospitalization, agreement on application of the law and the diagnostic evaluation to assess whether the admissions were appropriate. Methods Retrospective, record based, descriptive study comprising 101 psychiatric acute referrals from the Tromsø Casualty Clinic to the psychiatric acute wards at the University Hospital of North Norway. Results The specialists accepted all referrals except one, they mostly agreed upon the diagnoses suggested by the referring doctors and they mostly confirmed the application of the law. Seventy-five percent of the admissions took place during weekends, public holidays or nighttimes. Diagnoses of psychoses or suicidal attempts accounted for 76 % of the total referrals. Substance abuse was noted for 43 %, and in 22 % of all admissions the patients had stopped taking their psychopharmacological medication. The police assisted the referring doctors in one third of all admissions, and was the legal representative in 52 out of 59 involuntary admissions. Thirty percent of the admissions were first- time admissions. Thirty-two percent of the hospital stays lasted for three days or less. Median length of stay was 6.5 days. Conclusion The casualty clinic physicians and the hospital specialists mostly agreed in their evaluation of patients indicating that most of the admissions were appropriate. The police was more often involved in the involuntary admissions than intended in the law. The proportion of patients with substance abuse was significant. Alternative treatment strategies should be developed for non-psychotic patients in need of short-term stays.